Design of HDPE‐based nanocomposite with excellent thermal‐oxidative aging resistance, mechanical properties and electrical insulation properties: Dispersing nano‐ZnO assisted by natural rubber latex - Li, Jinglin; Mou, Wenjie; Zhu, Jinxin; Hu, Chaoqiang (Journal of applied polymer science, 2023)
Modification with nanoparticles is an effective way of overcoming the inherent defects of high‐density polyethylene (HDPE). However, the uniform dispersion of nanoparticles in the polymer matrix is the key point of this method. Here, natural rubber latex (NRL) was used for the auxiliary dispersion of self‐made nano zinc oxide (nano‐ZnO) to realize the uniform dispersion of nano‐ZnO in HDPE. The HDPE‐based nanocomposite with excellent thermo‐oxidative aging resistance, mechanical properties and electrical insulation properties were successfully prepared. Three weight percent of nano‐ZnO was uniformly dispersed in HDPE (HLZ3), which not only synergistically toughened HDPE with natural rubber (coagulated natural rubber latex, NR), but also maintained the tensile strength of the matrix. Moreover, the interfacial interactions between nanoparticles and polymers improved the alternating current (AC) breakdown strength and volume resistivity of the HDPE matrix. After aging treatment, the crystallinity of HLZ3 decreased very little, and its carbonyl index was much smaller than that of pure HDPE. Therefore, it has the best performance retention rate. This nanoparticle dispersion method has certain reference significance. And this HDPE‐based nanocomposite material is expected to be used in the outer sheath of cables. Under the auxiliary dispersion of natural rubber latex, nano‐ZnO is uniformly dispersed in HDPE, which not only synergistically toughens HDPE with natural rubber, but also improves the thermo‐oxidative aging resistance and electrical insulation properties of HDPE.